PENGARUH PROMOSI, ATRIBUT PRODUK, DAN LOYALITAS KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DI TOKOPEDIA - Veronika Veronika; Nora Pitri Nainggolan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to find out how promotions, product attributes, and consumer loyalty affect purchasing decisions at Tokopedia. In this study, the number of consumer respondents taken was 100 respondents as the research population using a questionnaire data collection technique. Analyze and process data using the SPSS application version 25. The effect of promotions on purchasing decisions at Tokopedia with a T count of 1.692 > T table of 1.984, the effect of product attributes on purchasing decisions at Tokopedia with a T count of 3.196 > T table of 1.984, and consumer loyalty to purchasing decisions at Tokopedia with a T count of 5.656 > T table of 1.984. From the results of the study it can be seen that promotions have no effect on purchasing decisions at Tokopedia while product attributes and consumer loyalty have an effect on purchasing decisions on Tokopedia. The calculated F value obtained is 61.351> from F table 2.70. From the results of the study it can be shown that promotion variables, product attributes and consumer loyalty simultaneously influence purchasing decisions at Tokopedia.